The role of GNAS1 gene polymorphisms in development of bladder and prostate cancer: A case–control study - A. N. Ayoob; Z. H. Abd Al-Wahid; A. I. Al-Badran (Regulatory Mechanisms in Biosystems, 2025)
GNAS gene encod es G-protein alpha subunit (Gαs) in humans. T393C polymorphism of GNAS1 is associated with Gαs pr o duction and augmented cAMP synthesis. Heterotrimeric G protein can stimulate the adenylyl cyclase, then leading to cAMP pr o duction in cells, which is crucial in many transduction pathways that are associated to proapoptotic mechanisms in cancer cells. The objective of our research was to clarify a potential correlation between T393C SNP of the GNAS1 gene and b ladder cancer (BC) and prostate cancer (PC) . GNAS1 genotyping in one hundred and twenty-four cases and one hundred controls w as examined by PCR. We examined the d istribution of GNAS1 gene alteration in BC patients and compared it with the control group , which showed the risk for BC was elevated two fold in the patients with TC and was elevated n ine fold in the patients with CC a llele (95% CI – 1.094 – 4.028 and 1 .000– 88.054 respectively ) . The risk factor increased about 2 fold with PC patients with the TC allele (95% CI – 1.445 – 5.535), and about 6 fold in the patients with the CC allele (95% CI – 0.501 – 67.4 00 ). This paper exhibited a significant rel a tionship of GNAS1 gene alterations with BC and PC , in particular TT and CT alleles may be a sign of propensity for BC and PC.